2019
DOI: 10.1038/s41467-019-08450-4
|View full text |Cite
|
Sign up to set email alerts
|

MANF antagonizes nucleotide exchange by the endoplasmic reticulum chaperone BiP

Abstract: Despite its known role as a secreted neuroprotectant, much of the mesencephalic astrocyte-derived neurotrophic factor (MANF) is retained in the endoplasmic reticulum (ER) of producer cells. There, by unknown mechanisms, MANF plays a role in protein folding homeostasis in complex with the ER-localized Hsp70 chaperone BiP. Here we report that the SAF-A/B, Acinus, and PIAS (SAP) domain of MANF selectively associates with the nucleotide binding domain (NBD) of ADP-bound BiP. In crystal structures the SAP domain en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
79
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(91 citation statements)
references
References 62 publications
11
79
0
Order By: Relevance
“…Consistent with our network, MANF has conserved, divergent genetic interactions with XBP1 and EIF2AK3, but not ATF6 (Lindstrom et al, 2016). Moreover, MANF was recently identified to stabilize a subset of HSPA5-client complexes in the ER lumen (Yan et al, 2019). Indeed, HSPA5 is highly coessential with MANF in addition to correlating with XBP1 and anticorrelating with EIF2AK3, supporting a model in which MANF is a point of regulation between the functionally differentiated branches of the UPR.…”
Section: Identifying Topology and Crosstalk Between Functional Modulesupporting
confidence: 86%
“…Consistent with our network, MANF has conserved, divergent genetic interactions with XBP1 and EIF2AK3, but not ATF6 (Lindstrom et al, 2016). Moreover, MANF was recently identified to stabilize a subset of HSPA5-client complexes in the ER lumen (Yan et al, 2019). Indeed, HSPA5 is highly coessential with MANF in addition to correlating with XBP1 and anticorrelating with EIF2AK3, supporting a model in which MANF is a point of regulation between the functionally differentiated branches of the UPR.…”
Section: Identifying Topology and Crosstalk Between Functional Modulesupporting
confidence: 86%
“…Manf inactivation causes upregulation of ER stress and UPR markers in the cochlear sensory cells MANF physically interacts with the ER chaperone GRP78 and this complex antagonizes ER stress caused by protein folding defects 7,8 . To find out if GRP78 is upregulated in Manf-inactivated cochleas, similar as shown in the pancreas 4 , we stained cochlear sections from 8-weekold mice with the GRP78 antibody.…”
Section: Conditional Inactivation Suggests a Local Function For Manf mentioning
confidence: 99%
“…MANF resides in the endoplasmic reticulum (ER) where it promotes protein-folding homeostasis 6 . MANF interacts physically with the major ER chaperone, the 78 kDa glucose-regulated protein (GRP78; also known as the binding immunoglobulin protein, BiP) 7,8 . Proteostasis defects trigger GRP78 and MANF upregulation, in conjunction with the activation of the unfolded protein response (UPR) and calcium release from the ER stores 9,10 .…”
Section: Introductionmentioning
confidence: 99%
“…We previously showed that Grp78 and MANF interact directly with each other in cardiac myocytes 14,15 . Moreover, another study has shown that MANF interacts with Grp78 in vitro in a way that affects the chaperone activity of Grp78 in a manner predicted to improve ER proteostasis, in vivo 63 . In combination with that study, our results here demonstrate that MANF can improve ER protein-folding by interacting with Grp78, and MANF can act as a chaperone itself, suggesting that there may be multiple ways that MANF improves ER protein-folding and cardiac myocyte viability during reductive stresses, such as I/R and DTT.…”
Section: Manf Represents a Novel Class Of Chaperonesmentioning
confidence: 99%